Building trust in digital policing: a scoping review of community policing apps. (27th July 2021) - Elphick, Camilla; Philpot, Richard; Zhang, Min; Stuart, Avelie; Walkington, Zoe; Frumkin, Lara A.; Pike, Graham; Gardner, Kelly; Lacey, Mark; Levine, Mark; Price, Blaine; Bandara, Arosha; et al.
ABSTRACT: Perceptions of police trustworthiness are linked to citizens' willingness to cooperate with police. Trust can be fostered by introducing accountability mechanisms, or by increasing a shared police/citizen identity, both which can be achieved digitally. Digital mechanisms can also be designed to safeguard, engage, reassure, inform, and empower diverse communities. We systematically scoped 240 existing online citizen-police and relevant third-party communication apps, to examine whether they sought to meet community needs and policing visions. We found that 82% required registration or login details, 55% of those with a reporting mechanism allowed for anonymous reporting, and 10% provided an understandable privacy policy. Police apps were more likely to seek to reassure, safeguard and inform users, while third-party apps were more likely to seek to empower users. As poorly designed apps risk amplifying mistrust and undermining policing efforts, we suggest 12 design considerations to help ensure the development of high quality/fit for purpose Police/Citizen apps.